2013
DOI: 10.1161/circulationaha.113.001437
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Race and Ethnicity on Outcomes With Drug-Eluting and Bare Metal Stents

Abstract: We sought to evaluate long-term PCI outcomes for racial and ethnic minorities in the modern era, as well as DES use, safety, and effectiveness, using a large nationally representative patient sample. We examined data from the National Cardiovascular Data Registry CathPCI Registry linked to Medicare claims data to identify any differences in patterns of DES and BMS use among racial and ethnic groups, to describe and compare outcomes after PCI for each racial and ethnic group, and to assess comparative long-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 26 publications
(46 reference statements)
2
39
0
Order By: Relevance
“…9,[55][56][57] Although East Asian patients have a higher prevalence of high on-treatment platelet reactivity during clopidogrel treatment than white patients, 9,51 the incidence of adverse ischaemic outcomes or stent thrombosis after PCI is similar or lower than that in white patients. [58][59][60][61] Analysis of data from the US National Cardiovascular Data Registry showed that Asian patients undergoing coronary stent implantation had a lower adjusted risk for the compo site end point of death, MI, and repeat revascularization than white patients (HR 0.89, 95% CI 0.82-0.96, P value not given). 58 In this analysis, the individual end point of death was slightly lower in Asian patients than in white patients, and the incidence of MI was similar in each group.…”
Section: Consensus Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[55][56][57] Although East Asian patients have a higher prevalence of high on-treatment platelet reactivity during clopidogrel treatment than white patients, 9,51 the incidence of adverse ischaemic outcomes or stent thrombosis after PCI is similar or lower than that in white patients. [58][59][60][61] Analysis of data from the US National Cardiovascular Data Registry showed that Asian patients undergoing coronary stent implantation had a lower adjusted risk for the compo site end point of death, MI, and repeat revascularization than white patients (HR 0.89, 95% CI 0.82-0.96, P value not given). 58 In this analysis, the individual end point of death was slightly lower in Asian patients than in white patients, and the incidence of MI was similar in each group.…”
Section: Consensus Statementsmentioning
confidence: 99%
“…[58][59][60][61] Analysis of data from the US National Cardiovascular Data Registry showed that Asian patients undergoing coronary stent implantation had a lower adjusted risk for the compo site end point of death, MI, and repeat revascularization than white patients (HR 0.89, 95% CI 0.82-0.96, P value not given). 58 In this analysis, the individual end point of death was slightly lower in Asian patients than in white patients, and the incidence of MI was similar in each group. The incidence of stent thrombosis reported in South Korean and Japanese registries (~0.2% per year) is lower than that in Western registries (~0.6% per year) after first-generatio n drugeluting stent implantation.…”
Section: Consensus Statementsmentioning
confidence: 99%
“…12 The lack of appropriate use of evidence-based therapies after PCI may partially contribute to the excess morbidity and mortality reported among minorities. 13,14,6 The improvement of medication adherence is a global priority, 15 yet only a few experimental interventions have been proven to be successful. 16 These include interventions that reduce out-of-pocket costs, simplify regimens, facilitate delivery of medications, or offer behavioral support.…”
Section: Introductionmentioning
confidence: 99%
“…The finding that African-American patients are less likely to receive DES than Caucasians has been observed in prior studies. [67813] However, our study shows that when insurance is uniform, DES utilization is similar in African-American and Caucasian predominant areas. This could be due to similar utilization of DES in Caucasian and African-American HRRs despite variation in prevalence of comorbid conditions and socioeconomic milieu or an underutilization of DES in African-American dominant HRRs compared to Caucasian HRRs.…”
Section: Discussionmentioning
confidence: 64%